Remaking signs and potentials for learning in L2 multimodal composing - Jantasin, Pattaramas; Satar, Müge (Technology in Language Teaching & Learning, 2025)
Multimodal composing activities invite language learners to draw upon distinct potentials of diverse modes of representation to make and remake signs for communication. Despite increased interest in incorporating multimodal composing activities in language classrooms, we do not yet have an in-depth understanding of the process of remaking signs and its implications on the meaning being expressed and potentials for learning. To address this gap, we investigate multimodal composing activities of 25 undergraduate students in one EFL classroom in Thailand, who designed digital posters of an innovative product in small groups and delivered in-class presentations. Through social semiotic analysis of the posters and video recordings of the presentations by two groups, and drawing on the notion of ‘writing as design’, we examine specific changes in meaning representation (gains and losses) during multimodal composing. Our findings reveal that remaking signs across different modes shaped not only the meaning being expressed, but also what became available for students to learn and how. Our conclusion emphasizes the need for teachers to fully utilize modes available in all learning environments to best support students in achieving their communicative and learning objectives.